Is Xenopus laevis introduction linked with Ranavirus incursion, persistence and spread in Chile? - Peñafiel Ricaurte, Alexandra.; Price, Stephen J.; Leung, William T.M.; Alvarado Rybak, Mario Andrés.; Espinoza Zambrano, Andrés.; Valdivia, Catalina; Cunningham, Andrew A.; Azat, Claudio (PeerJ Inc., 2023)
Ranaviruses have been associated with amphibian, fish and reptile mortality events worldwide and with amphibian population declines in parts of Europe. Xenopus laevis is a widespread invasive amphibian species in Chile. Recently, Frog virus 3 (FV3), the type species of the Ranavirus genus, was detected in two wild populations of this frog near Santiago in Chile, however, the extent of ranavirus infection in this country remains unknown. To obtain more information about the origin of ranavirus in Chile, its distribution, species affected, and the role of invasive amphibians and freshwater fish in the epidemiology of ranavirus, a surveillance study comprising wild and farmed amphibians and wild fish over a large latitudinal gradient (2,500 km) was carried out in 2015–2017. In total, 1,752 amphibians and 496 fish were tested using a ranavirus-specific qPCR assay, and positive samples were analyzed for virus characterization through whole genome sequencing of viral DNA obtained from infected tissue. Ranavirus was detected at low viral loads in nine of 1,011 X. laevis from four populations in central Chile. No other amphibian or fish species tested were positive for ranavirus, suggesting ranavirus is not threatening native Chilean species yet. Phylogenetic analysis of partial ranavirus sequences showed 100% similarity with FV3. Our results show a restricted range of ranavirus infection in central Chile, coinciding with X. laevis presence, and suggest that FV3 may have entered the country through infected X. laevis, which appears to act as a competent reservoir host, and may contribute to the spread the virus locally as it invades new areas, and globally through the pet trade.
Keywords: African clawed frog; Emerging infectious disease; Frog Virus 3; Ranavirus; Anfibios; Embalses